Design of a Competency Evaluation Model for Clinical Nursing Practicum, Based on Standardized Language Systems: Psychometric Validation Study - Iglesias-Parra, María Rosa; García-Guerrero, Alfonso María; García-Mayor, Silvia; Kaknani-Uttumchandani, Shakira; León-Campos, Álvaro; Morales-Asencio, José Miguel (Sigma, 2015)
Abstract Purpose: To develop an evaluation system of clinical competencies for the practicum of nursing students based on the Nursing Interventions Classification (NIC). Design and Methods: Psychometric validation study: the first two phases addressed definition and content validation, and the third phase consisted of a cross-sectional study for analyzing reliability. The study population was undergraduate nursing students and clinical tutors. Findings: Through the Delphi technique, 26 competencies and 91 interventions were isolated. Cronbach’s α was 0.96. Factor analysis yielded 18 factors that explained 68.82% of the variance. Overall inter-item correlation was 0.26, and total–item correlation ranged between 0.66 and 0.19. Conclusions: A competency system for the nursing practicum, structured on the NIC, is a reliable method for assessing and evaluating clinical competencies. Further evaluations in other contexts are needed. Clinical Relevance: The availability of standardized language systems in the nursing discipline supposes an ideal framework to develop the nursing curricula.
Keywords: Estudiantes de enfermería - Competencias y funciones; Clinical teaching (health education); competency-based education; nursing education; performance; student evaluation; practicums